Chronic histiocytic intervillositis in consecutive miscarriages: A potential pitfall in routine examination of conceptus - Siti Khadijah Mohd Fuad; Nazifah Adznan; Abd Rahman Hayati; Vikneswaran Virasamy; Nur Syahrina Rahim (Academy of Medicine Malaysia, 2024)
Indexed by WOS/MyCite